Specific Methods of Information Security for Nuclear Materials Control and Accounting Automate Systems - Konstantin Vyacheslavovich Ivanov (Bezopasnostʹ Informacionnyh Tehnologij, 2013)
The paper is devoted to specific methods of information security for nuclear materials control and accounting automate systems which is not required of OS and DBMS certifications and allowed to programs modification for clients specific without defenses modification. System ACCORD-2005 demonstrates the realization of this method.